Sustainability and Complementarity of Agriculture and Rural Areas in the EU - Svoboda, Jaroslav; Faltová Leitmanová, Ivana; Jiří Alina, Jiří Alina (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
The main tasks of agriculture are undoubtedly food production and fulfilling its non-productive functions. This complementarity is realised particularly in the rural area. The aim of this paper is to evaluate the economic performance of selected EU countries in terms of labour productivity in the rural space and agrarian space, first from a macroeconomic perspective. From a microeconomic perspective, the analysis is carried out for the average agricultural enterprises of the EU countries. The evaluation is carried out for the EU Member States from 2004 to 2022 using the Eurostat and FADN databases. A certain limitation was the Eurostat database, which does not contain complete data for all countries and years. Labour productivity was analysed using cluster analysis. It was found that there are significant differences in labour productivity of the average farm between the original EU member states and the new accession countries since 2004. The exclusion of subsidies caused a 15% decrease in labour productivity. Moreover, the findings are substantially influenced by the price level in each of the countries studied, as well as the degree of urbanisation and the share of Rural Areas in these countries.